The Dynamics of Communication Networks of Islamic Preaching Organizations in the New Media Era: A Review of the Phenomenon of Digital Preaching Trendsetters - Ikhwansyah Nasution; Muhammad Randicha Hamandia; Anang Anas Azhar; Elfi Yanti Ritonga; Zhila Jannati (Jurnal Administrasi Pemerintahan Desa, 2026)
The digital era has created a completely different way for religious messages to be distributed which has transformed the operation of da’wah authority. The system evolved from traditional institutional frameworks to contemporary virtual networks which individual users created. This research investigates how digital da’wah trendsetters use organizational communication network theory to study their activities within new media environments. Through a literature review this study wants to reconceptualize the structure of da’wah organizations that are no longer held back by institutional walls which is a boundaryless organization but instead are controlled by algorithms and the node centrality of a trendsetter. The conceptual findings show that trendsetters on social media like YouTube and Instagram and TikTok actually function as Top Management in a virtual organization! The followers in this arrangement function as subordinates who willingly choose to reproduce and distribute and validate the da’wah messages. This dynamic creates a flow of information that is just massive and it is vulnerable to algorithmic bias and the fragmentation of religious authority. This article provides a conceptual synthesis that positions da’wah social media accounts as more than just media channels. The social media accounts function as an organizational communication ecosystem which has its own organizational structure that operates through hidden power dynamics and organizational culture.